Contribution to the knowledge of the genus Dicronychus (Coleoptera: Elateridae) from the Kingdom of Saudi Arabia - Dhafer, Hathal M. Al; Platia, Giuseppe (Zootaxa, 2013)
Examination of specimens of Dicronychus Brullé in the King Saud University Museum of Arthropods, Riyadh, Saudi Arabia revealed the presence of two new species, D. latifae n. sp. and D. bushrae n. sp. In addition, the descriptions of D. talhouki Platia and Schimmel and D. brancuccii Platia and Schimmel are augmented after examination of both type material and recently collected specimens from the Kingdom of Saudi Arabia.